Portraits from Above: Hong Kong's Informal Rooftop Communities - Canham, Stefan; Rufina, Wu; Papaioannou, Hercules (Design/Arts/Culture, 2023)
Rufina Wu and Stefan Canham's series, "Portraits from Above, Hong Kong's Rooftop Informal Communities" (2007-2008), meticulously examines the overlooked urban phenomenon of unauthorized rooftop dwellings in Hong Kong's central districts. Focusing on the makeshift homes constructed by migrants in search of affordable housing, the series unveils a unique social and architectural history often unnoticed at street level. Through a comprehensive approach encompassing photographs, architectural drawings, and interviews, Wu and Canham unveil a world shaped by personal necessity and characterized by its ephemeral yet enduring nature. The series captures the juxtaposition of these informal settlements against the sleek skyscrapers, revealing the invisible slums within the heart of Hong Kong. The work provides a nuanced analytical perspective on the sociocultural pressures of the modern metropolis while highlighting the resilience of communities existing under the shadow of the law. Wu and Canham's documentation offers a tangible portrayal of real people navigating a world teetering between hope and despair.